PEACE IS THE HIGHEST GOOD (Web of Teachers: Inderscience Research, 2025)
This article examines the concept of peace as the highest good in the context of philosophy, ethics, and contemporary societal challenges. Using an interdisciplinary approach, the author shows that a stable world is necessary for the realization of human potential, economic development, and cultural prosperity. The key philosophical foundations of the idea of peace are presented, cultural and legal aspects are considered, and possible directions for strengthening peace initiatives are proposed.